Full Slime Cyanidation Leaching of the Primary Gold Ore from a Metallurgical Processing Plant in Gansu - Yanbo CHEN; Guangsheng LI; Xingfu ZHU; Qing XU (Kuangchan zonghe liyong, 2024)
This is an article in the field of metallurgical engineering. A beneficiation and smelting plant processes two kinds of gold ores: primary ore and oxidized ore. The primary ore is treated by conventional flotation process. The gold recovery rate of flotation concentrate is about 85%, which is sold to smelting enterprises outside the province for cyanide leaching. The oxidized ore is treated by stirring cyanidation leaching activated carbon adsorption gold loaded carbon analytical electrodeposition gold slime smelting ingot casting process. The output gold ingot is sold outside, and the total recovery rate of gold dressing and metallurgy is about 90%. At present, with the deepening of mining depth, the ore properties change, the amount of oxidized ore gradually decreases, and the amount of primary ore gradually increases, resulting in excessive ore treatment in flotation system and insufficient ore treatment in leaching system, affecting the economic benefits of enterprises. Therefore, the enterprise considers adding the primary ore that cannot be treated by the flotation system to the existing oxidized ore all slime cyanidation leaching system to increase the gold ingot output and economic benefits of the enterprise. In order to enable the existing full slime cyanidation leaching system to leach the primary ore, based on the field investigation, the grinding fineness, reagent dosage and dissolved oxygen condition tests were carried out for the primary ore, and the alkali leaching pretreatment test and mixed oxidation ore leaching test were carried out in combination with the actual production. Based on these test and research results, specific rectification requirements and measures are put forward for the production site.